2012
DOI: 10.1590/s1806-83242012000700015
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dental caries on preschool children's quality of life: an update

Abstract: The literature reports that dental caries can cause functional, physical and aesthetic impairment, often with repercussions on children's general health at an early age. Moreover, recent studies have investigated how caries lesions can compromise children's quality of life. This paper aims to describe the current situation of dental caries prevalence in children and how this oral health disease can impact their quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
26

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 34 publications
1
59
0
26
Order By: Relevance
“…The following five-point rating scale was used: never = 0; once/twice = 1; sometimes = 2; often = 3 and every day/almost every day = 4. CPQ [8][9][10] scores were calculated by adding the scores of all items, yielding a total score from 0 (no impact of oral condition on OHRQoL) to 100 (maximum impact of oral condition on OHRQoL). For the statistical analysis, the impact on OHRQoL was classified as either low (CPQ 8-10 ≤ 10) or high (CPQ 8-10 > 10) based on the median value of CPQ 8-10 total score.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following five-point rating scale was used: never = 0; once/twice = 1; sometimes = 2; often = 3 and every day/almost every day = 4. CPQ [8][9][10] scores were calculated by adding the scores of all items, yielding a total score from 0 (no impact of oral condition on OHRQoL) to 100 (maximum impact of oral condition on OHRQoL). For the statistical analysis, the impact on OHRQoL was classified as either low (CPQ 8-10 ≤ 10) or high (CPQ 8-10 > 10) based on the median value of CPQ 8-10 total score.…”
Section: Data Collectionmentioning
confidence: 99%
“…6 It is suggested that the measurement of Oral Health-Related Quality of Life (OHRQoL) should be an essential component of oral health surveys. 7 However, most studies addressing the pediatric population involve preschool children 3,8,9,10 or those whose permanent dentition is fully established. 11,12,13 Few studies 14,15,16 have been conducted with children in the mixed dentition stage.…”
Section: Introductionmentioning
confidence: 99%
“…A healthy smile has considerable bearing on social interaction, which plays an important role in how children are seen, felt and perceived by others 30 . ETW was diagnosed in 51.2% of the children in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Dental caries belongs to the most common chronic disease in childhood [4][5][6]. Between preventive dental care and tooth decay-related expenditures was not found significantly association [7].…”
Section: Introductionmentioning
confidence: 97%